2011
DOI: 10.1523/jneurosci.2745-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

A Shh/miR-206/BDNF Cascade Coordinates Innervation and Formation of Airway Smooth Muscle

Abstract: Dysfunctional neural control of airway smooth muscle (ASM) is involved in inflammatory diseases, such as asthma. However, neurogenesis in the lung is poorly understood. This study uses mouse models to investigate developmental mechanisms of ASM innervation, a process that is highly coordinated with ASM formation during lung branching morphogenesis. We show that brain-derived neurotrophic factor (BDNF) is an essential ASM-derived signal for innervation. Although BDNF mRNA expression is temporally dissociated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 42 publications
4
75
0
Order By: Relevance
“…The importance of the crosstalk between miRNAs and the Shh signaling pathway during embryonic development is increasingly recognized (25,26). We reported that brain-derived neurotrophic factor is a target of miR-206.…”
Section: Clinical Relevancementioning
confidence: 98%
See 3 more Smart Citations
“…The importance of the crosstalk between miRNAs and the Shh signaling pathway during embryonic development is increasingly recognized (25,26). We reported that brain-derived neurotrophic factor is a target of miR-206.…”
Section: Clinical Relevancementioning
confidence: 98%
“…We reported that brain-derived neurotrophic factor is a target of miR-206. Shh induces the expression of brain-derived neurotrophic factor by suppression of miR-206 in the formation and innervation of airway smooth muscle cells (26). miR-214 is expressed in somites of Zebrafish during early stages of segmentation and plays a role in muscle cell fate specification by down-regulating the expression of Sufu, a negative regulator of Hedgehog signaling (25).…”
Section: Clinical Relevancementioning
confidence: 99%
See 2 more Smart Citations
“…The PCLSs were then embedded in optical cutting temperature compound and sectioned to 10-mm-thick slices. Using a previously established protocol (28), the slices were immunostained with antibodies against the lung epithelium marker CC10 (1:500, T-18; Santa Cruz Biotechnology, Santa Cruz, CA) and the ASM marker a-smooth muscle actin (1:500, MS-113; Thermo Fisher Scientific). Viability is preserved in frozen-thawed precision-cut lung slice (PCLS).…”
Section: Preparation and Immunohistology In Thin Sections Of Pclsmentioning
confidence: 99%